The effect of strategic human resource management practices on performance of manufacturing multinational companies in Kenya: moderating role of employee cultural orientations and mediating role of employee motivation - Dimba, Beatrice A; K’Obonyo, Peter (My University, 2009)
This study linked strategic human resource (SHRM) practices, cultural orientations, employee motivation and firm performance in foreign manufacturing multinational companies (MNCs) in Kenya. The objectives were: to establish the relationship between SHRM practices and firm performance; to determine the extent to which the relationship between SHRM practices and employees’ motivation depends on employees’ cultural orientations; to establish if the relationship between SHRM practices and firm performance is mediated by employees’ motivation; to gauge the relationship between motivation and firm performance. The respondents were HR managers, marketing managers and production managers, and nonmanagement employees working in 50 foreign MNCs. Data was collected using questionnaires developed by Hofstede and Huselid and modified by the researcher. Hofstede’s instrument contains measures of employees’ cultural orientations, whereas Huselid’s instrument contains measures for SHRM practices, motivation and performance. The findings of the study indicate that: all the variables of SHRM practices, except recruitment and selection were positively and significantly correlated with performance; relationship between SHRM practices and firm motivation did not depend on employee cultural orientations in the case where cultural beliefs were considered, but depended on employee cultural orientations when cultural values were considered; motivation mediated relationship between SHRM practices and firm performance; and motivation affected firm performance.
Keywords: Strategic human resource management; Manufacturing Multinational Companies; Kenya; Employee motivation